Vocational Education and the Development of Adult Learners in Nigeria Through Skills Acquisition Schemes - B. Ubong; N.S. Oguzor (University of Sofia, 2007)
A number of persons in any society may not, in spite of the availability of chances for education, acquire formal education up to the level that would position them for sustained personal growth in paid employment or in self-employment. Also, the concept of life-long learning requires continuous exposure to methods and knowledge generally in the chosen trade or profession of the individual. Programmes are therefore designed to meet the needs of persons that did not acquire enough formal education or none at all as well as those that need to sustain learning for self-development. Skills acquisition programmes are therefore designed under structured programmes of adult education to meet the needs of adult learners. This paper reviews the concepts of adult education and skills acquisition, the latter as an aspect of adult education with emphasis on Nigeria. It reviews a case involving a tertiary institution in Nigeria as sponsored by petroleum producing companies. The paper highlights the need for greater emphasis on practice during training under skills acquisition.